2013
DOI: 10.1049/iet-map.2011.0564
|View full text |Cite
|
Sign up to set email alerts
|

Millimetre‐wave path‐loss variability between two body‐mounted monopole antennas

Abstract: Variation of on‐body millimetre‐wave propagation channels with body movements has been studied experimentally. A statistical description of the propagation channel is presented, including path‐loss probability distributions, level‐crossing rates and average fade durations. The median path losses for the considered practical links with omnidirectional monopole antennas lied within the range of 55–88 dB. The signal variation was found to consist of two superimposed variations, in general: the long‐term and short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
(13 reference statements)
1
14
0
Order By: Relevance
“…Nevertheless, we shall separate the two types of temporal signal variation for both the antenna types and compare the statistics for the two cases. This has been done for the monopole antennas in [3]. The same procedure have been used in this paper, i.e.…”
Section: Comparison Of the Links With The Monopolesmentioning
confidence: 99%
“…Nevertheless, we shall separate the two types of temporal signal variation for both the antenna types and compare the statistics for the two cases. This has been done for the monopole antennas in [3]. The same procedure have been used in this paper, i.e.…”
Section: Comparison Of the Links With The Monopolesmentioning
confidence: 99%
“…As one of the key components in the communication system, wearable antennas have received much attention in both academia and industry since their unconventional operating environment is in extremely close proximity to the human body [4]. In this case, the loading of lossy human tissue makes the design of a high radiation efficiency antenna challenging when it is also desirable for it to possess light-weight and low-profile characteristics [5,6]. Simultaneously, the impact of a wearable antenna on human tissue, characterized by the specific absorption rate (SAR), also needs to be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…BANs rely, theoretically, on Norton's investigation of radio communication using small antennas [1]. An increasing number of research works deals with the development of mmWave BANs, identified as a highly attractive solution for future wireless BAN (WBANs), with a strong potential in health care environments, entertainment, identification systems, sports, smart homes, space and military applications [2]- [4].…”
Section: Introductionmentioning
confidence: 99%